Takotsubo cardiomyopathy in an ultra-centenarian woman - Bonfanti, Laura; Buratti, Silvia; Vignali, Luigi; Lippi, Giuseppe; Masini, Franco; Bianconcini, Michele; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2018)
A 101 years-old woman was admitted to our Emergency Department (ED) for acute dyspnea which onset nearly two hours before presentation. She had been on hydrochlorothyazyde-amiloride therapy due to mild hypertension. No other relevant features were present in the clinical history. The old lady had never been admitted to the hospital, and she was still living alone. A few days before hospital admission, one of the daughters became ill, so that a caregiver was paid for assisting her 12/24. This new circumstance was reluctantly accepted by the old lady. At ED presentation the patient was dyspnoic but alert. The electrocardiogram showed a marked elevation of the ST segment in V2-V6 leads. The echocardiogram showed the typical apical ballooning, characteristic of takotsubo cardiomyopathy. Blood test only showed a significant increase of cardiac troponin I. Considering the very good conditions of the patient, a coronary angiography was performed, that demonstrated a coronary tree totally free of lesions, thus confirming the clinical suspicion of takotsubo syndrome. The patient was admitted to the Coronary Care Unit, where she had a very good clinical course, and was discharged on day 6th after presentation. After one month of follow-up the clinical course was uneventful and the lady remained in good clinical and lifestyle conditions as before presenting to the ED. This unique case attests that takotsubo cardiomyopathy can be also observed at extreme ages, and should hence be considered in the differential diagnosis of acute dyspnea and chest pain in extremely elderly patients.